Phosphorus Dynamics in Sugarcane Fertilized With Filter Cake and Mineral Phosphate Sources - de Aquino Vidal Lacerda Soares, Anelisa; de Mello Prado, Renato; Caione, Gustavo; Rodrigues, Marcos; Pavinato, Paulo Sérgio; Naudi Silva Campos, Cid (Frontiers in Soil Science, 2021)
Organic residual material such as filter cake, combined with mineral phosphate fertilizers, may alter the soil P bioavailability for sugarcane as consequence of the competing effect in adsorption sites. This study aimed to quantify the changes in both the inorganic and organic soil P fractions as amended by P fertilizer sources phosphate and filter cake, and link the P fractions to sugarcane response. An experiment was conducted in an Oxisol, in a randomized block design with factorial arrangement of 4x2, and three replications. Three P fertilizer sources (triple superphosphate, Araxá rock phosphate, and Bayóvar® reactive phosphate) plus a control (no P) were evaluated under both the presence and absence of filter cake. At the end of the second crop cycle, it was measured the cane yield, the tissue P content, and soil remaining P fractions. All P fertilizer sources were efficient in supplying P to the sugarcane. Araxá rock phosphate generated a higher accumulation moderately labile P, whereas the soluble triple superphosphate resulted in higher labile P. The filter cake, as a source of nutrients and organic matter, have an important contribution to maintain more available P for sugarcane absorption, especially when associated to triple superphosphate. The amount of P absorbed by sugarcane was correlated with the soil labile P fractions (r = 0.58), and also with the inorganic P moderately labile (r = 0.42). Both fractions must be taken into account for a short to medium-term availability of P for sugarcane in Oxisols.